Is Obesity an Independent Barrier to Obtaining Prenatal Care? - Levine, Lisa D.; Landsberger, Ellen J.; Bernstein, Peter S.; Chazotte, Cynthia; Srinivas, Sindhu K. (American Journal of Perinatology, 2013)
Objective Obesity is a demonstrated barrier to obtaining health care. Its impact on obtaining prenatal care (PNC) is unknown. Our objective was to determine if obesity is an independent barrier to accessing early and adequate PNC.Study Design We performed a retrospective cohort study of women who initiated PNC and delivered at our institution in 2005. Body mass index (BMI) was categorized by World Health Organization guidelines: underweight (<18.5 kg/m2), normal weight (18.5 to 24.9 kg/m2), overweight (25.0 to 29.9 kg/m2), and obese (≥30 kg/m2). Maternal history and delivery information were obtained through chart abstraction. Differences in gestational age at first visit (GA-1) and adequate PNC were evaluated by BMI category. Data were compared using χ2 and nonparametric analyses.Results Overall, 410 women were evaluated. The median GA-1 was 11.1 weeks and 69% had adequate PNC. There was no difference in GA-1 or adequate PNC by BMI category (p = 0.17 and p = 0.66, respectively). When BMI groups were dichotomized into obese and nonobese women, there was no difference in GA-1 or adequate PNC (p = 0.41).Conclusion In our population, obesity is not an independent barrier to receiving early and adequate PNC. Future work is warranted in evaluating the association between obesity and PNC and the perceived barriers to obtaining care.
Keywords: obesity; access; adequate prenatal care